Longitudinal network analysis of mental health trends in Chinese university freshmen: a decadal study (2014–2023) - Teng, Xiujie; Wang, Xiaoyan; Liu, Ye; Wu, Dingchao; Dong, Zhenxuan; Lyu, Shaobo (Frontiers in Psychology, 2025)
IntroductionGlobal mental health deterioration among young adults is a growing concern. This study aims to map the psychopathological architecture of mental health symptoms in a large cohort of university freshmen to identify core symptoms that could be pivotal for intervention strategies.MethodsA network analysis was conducted on annual mental health assessments of 24,047 university freshmen over a ten-year period (2014–2023). Symptoms were assessed using the Symptom Checklist-90 (SCL-90).ResultsThe mental health symptom network structure demonstrated remarkable stability across the decade. Anxiety, depression, and interpersonal sensitivity were consistently identified as the most central symptoms within the network. The rank order of symptoms by nodal strength was: anxiety, depression, interpersonal sensitivity, psychoticism, obsessive symptoms, paranoia, hostility, phobia, and somatization.DiscussionThe findings highlight anxiety, depression, and interpersonal sensitivity as prominent and central psychological challenges for college students. The stability of this network structure suggests these core symptoms are reliable targets for priority screening and the development of targeted mental health interventions and preventative treatments within university populations.